Cadastral justification of land allotment in highway projects - Ємець, Олег Анатолійович (Technology audit and production reserves, 2014)
This article deals with the land allotment for construction of new highways and reconstruction of existing highways and their subsequent use. On the basis of current methods in highway sphere the parameters of sanitary protection zones after reconstruction of state highways have been defined in accordance with the parameters of international auto transport corridors in open terrain. The functional land zoning of auto transport corridors has been developed and the parameters of their rights of way have been defined with the appliance of environmental measures. The roadsides of various technical categories have been defined according to the directions of auto transport corridors with regard to the use of adjacent areas. The dimensions of reserved areas of auto transport corridors with implementation of environmental and public health protection measures have been justified, considering highway protection from the negative impact of processes and phenomena in the adjacent areas. The results of the research can be applied in planning of the network of international highways. Cadastral justification of land allotment will enable the rational use of the territory in road projects.